Joint audit 2019 : enhancing tax co-operation and improving tax certainty - Organisation for Economic Co-operation and Development (OECD, 2019)
Summary.
Keywords: verotus; tilintarkastus; yritysverotus; kansainvälinen vero-oikeus; verohallinto